The Analysis of Creative Thinking Ability of VII Class Student in Biology Learning at SMPN 25 (Junior High School 25) Padang - Widiawati Widiawati; Sa'diatul Fuadiyah; Syamsurizal Syamsurizal; Ardi Ardi (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Creative thinking is cognitive skill to gain knowledge. Creative thinking is a basic skill in educational process. Creative thinking is an ability to think of creating a new relationship that is more beneficial than previous information that already obtained. Research found out that creative thinking ability of class VII student in biology learning at SMPN 25 Padang was in moderate category.  Aspect of creative thinking that could be obtained by class VII student in highest percentage score was elaborative aspect. Overall, based on questionnaire, aspect of fluency could be obtained moderately with percentage of 59%; aspect of flexibility could be obtained moderately with percentage of 58%, aspect of originality could be obtained moderately with percentage of 59%, and aspect of elaborative could be obtained well with percentage of 60%. From research finding it was obtained average percentage of overall aspects was 59.2% that was in moderate category.